2021
DOI: 10.1080/07391102.2021.1927845
|View full text |Cite
|
Sign up to set email alerts
|

Proposition of a new allosteric binding site for potential SARS-CoV-2 3CL protease inhibitors by utilizing molecular dynamics simulations and ensemble docking

Abstract: The SARS-CoV-2 3CL protease (3CLpro) shows a high similarity with 3CL proteases of other beta-coronaviruses, such as SARS and MERS. It is the main enzyme involved in generating various non-structural proteins that are important for viral replication and is one of the most important proteins responsible for SARS-CoV-2 virulence. In this study, we have conducted an ensemble docking of molecules from the DrugBank database using both the crystallographic structure of the SARS-CoV-2 3CLpro, as well as five conforma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…Two studies reported that the Radotinib can be used for the prevention, alleviation, or treatment of viral respiratory disease. Specifically, the present invention can be used as a useful antiviral agent for the prevention or treatment of disease caused by infection of the SARS-CoV-2 and MERS-CoV [ 156 – 158 ]. A molecular docking simulation study suggested that Ivermectin may be an effective treatment for SARS-Cov2 infections [ 159 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported that the Radotinib can be used for the prevention, alleviation, or treatment of viral respiratory disease. Specifically, the present invention can be used as a useful antiviral agent for the prevention or treatment of disease caused by infection of the SARS-CoV-2 and MERS-CoV [ 156 – 158 ]. A molecular docking simulation study suggested that Ivermectin may be an effective treatment for SARS-Cov2 infections [ 159 ].…”
Section: Discussionmentioning
confidence: 99%
“…Present in the protease's catalytic dyads are other amino acids from CYS 145 and HIS 41, which are functional in eliminating Mpro enzymes. Dimerization and mutations of Mpro that engender enzymes with reduced activities are associated with interactions with the residues around GLU 288, ASP 289, and GLU 290 [59]. While CYS 145 and HIS 45 mediate the catalytic mechanism of the enzyme, mutation of these residues leads to the total annihilation of the Mpro activity [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Novak et al. 391 first screened 8756 approved or experimental drugs by regular docking; then the best 10 drugs from regular docking were further evaluated by an ensemble docking strategy. The 10 drugs were docked to 5 conformation representatives of Mpro obtained from MD simulations and cluster analysis.…”
Section: Methods and Approachesmentioning
confidence: 99%